CTRP1 Attenuates Cerebral Ischemia/Reperfusion Injury via the PERK Signaling Pathway - Fei, Huizhi; Xiang, Pu; Luo, Wen; Tan, Xiaodan; Gu, Chao; Liu, Maozhu; Chen, Mengyuan; Wang, Qiong; Yang, Junqing (Frontiers in Cell and Developmental Biology, 2021)
Cerebral ischemic stroke is one of the leading causes of death worldwide. Previous studies have shown that circulating levels of CTRP1 are upregulated in patients with acute ischemic stroke. However, the function of CTRP1 in neurons remains unclear. The purpose of this study was to explore the role of CTRP1 in cerebral ischemia reperfusion injury (CIRI) and to elucidate the underlying mechanism. Middle cerebral artery occlusion/reperfusion (MCAO/R) and oxygen- glucose deprivation/reoxygenation (OGD/R) models were used to simulate cerebral ischemic stroke in vivo and in vitro, respectively. CTRP1 overexpression lentivirus and CTRP1 siRNA were used to observe the effect of CTRP1 expression, and the PERK selective activator CCT020312 was used to activate the PERK signaling pathway. We found the decreased expression of CTRP1 in the cortex of MCAO/R-treated rats and OGD/R-treated primary cortical neurons. CTRP1 overexpression attenuated CIRI, accompanied by reduction of apoptosis and suppression of PERK signaling pathway. Interference with CTRP1 expression in vitro aggravated apoptotic activity and increased expression of proteins involved in the PERK signaling pathway. Moreover, activating the PERK signaling pathway abolished the protective effects of CTRP1 on neuron injury induced by CIRI in vivo and in vitro. In conclusion, CTRP1 protects against CIRI by reducing apoptosis and endoplasmic reticulum stress (ERS) through inhibiting PERK-dependent signaling pathway, suggesting that CTRP1 play a crucial role in the pathogenesis of CIRI.